Broadband access speeds across the Northern Powerhouse: A comparative analysis of English cities - Covadonga Gijon; Jason Whalley (International Telecommunications Society (ITS), 2018)
The UK economy is unbalanced, with the country's economic activity being dominated by London and the south-east of England. To address this imbalance, governments have initiated a series of initiatives aimed at creating a 'Northern Powerhouse' that will realise the north of England's economic potential. While the discussion around the realisation of the 'Northern Powerhouse' has highlighted the need for improved transportation infrastructure across the north of England, this has largely focused on rail or roads with little discussion of telecommunications. This paper seeks to overcome this surprising omission by focusing on the broadband speeds of Leeds and Newcastle, two cities located in the north of England. Using data from a variety of sources, our analysis demonstrates how broadband speeds vary within and between the two cities and are often worse than the UK average. Furthermore, our analysis of the relationship between affluence and broadband speeds in Newcastle reveals a complex picture that requires further investigation.
Keywords: 330; broadband; UK; Northern Powerhouse; digital divide